(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Hapida Y, Elfita, Widjajanti H, Salni. 2021. Biodiversity and antibacterial activity of endophytic fungi isolated from jambu bol (Syzygium malaccense). Biodiversitas 22: 5668-5677. Infectious diseases caused by pathogenic bacteria are still high. The existence of bacterial resistance to antibiotics makes it necessary to search for new antibacterial substances from plants and microorganisms. Syzygium malaccense (L.) Merr and Perry (Myrtaceae), known as jambu bol, has been used as a traditional medicine in Indonesia and other countries. It is used to treat pathogenic bacterial infections. Therefore, this study aims to determine the diversity of endophytic fungi and their potential as antibacterial compound sources compared to their host plants. Specifically, screening for endophytic fungi that have antibacterial activities is intended. In this study, endophytic fungi were isolated from the leaves, stem bark, and root bark of the host plants. Each isolate was identified morphologically and cultivated in potato dextrose broth (PDB) medium for four weeks. After the incubation period, the liquid culture was extracted with ethyl acetate and evaporated to obtain a concentrated extract. The Kirby-Bauer method was used to evaluate the antibacterial activity of each endophytic fungal extract and the host plant parts extract. The concentration used was 400µg/mL and the antibiotic was used as a positive control (Tetracycline) is 30µg/mL. Seven endophytic fungi were isolated from the leaves (YD1, YD2, YD3, YD4, YD6, YD7, Y2D1), seven from the stem bark (YB1, YB2, YB3, YB4, YB5, Y2B5, and Y2B6 ), and six from the root bark (YA1, YA2, YA3, YA4, YA5, Y2A2). The endophytic fungi were morphologically identified, and the isolates were shown to be dominated by genera from the Ascomycota (e.g., Poaceascoma, Cladorrhinum, Penicillium, Madurella, Phytophthora, Phialemonium, Monascus, Trichoderma, Ramophialophora, Gliocladium, Wiesneriomyces) and the Zygomycota (e.g., Mucor, Mortierella, and Gongronella) phyla. The fungi isolates Y2D1, YB1, and YA4 were shown to have the highest (strong) antibacterial activity equivalent to their hosts in the performed screening. Endophytic fungi have significant and continued antibacterial activities that have been identified molecularly.